The topological key lncRNA H2k2 from the ceRNA network promotes mesangial cell proliferation in diabetic nephropathy via the miR‐449a/b/Trim11/Mek signaling pathway. Issue 10 (23rd July 2019) - Chen, Wenyun; Peng, Rui; Sun, Yan; Liu, Handeng; Zhang, Luyu; Peng, Huimin; Zhang, Zheng
ABSTRACT: Evidence has shown that long noncoding RNAs (IncRNAs) in the competing endogenous RNA (ceRNA) network are involved in various diseases. However, there is a lack of studies of the ceRNA network in diabetic nephropathy (DN). In this study, we investigated the effect of IncRNAs on mesangial cell (MC) proliferation in DN‐related ceRNA networks. Differences in IncRNA and mRNA expression between DN and normal mouse kidney tissues were detected with RNA‐seq, and DN‐related IncRNA/mRNA/microRNA (miRNA) ceRNA networks were constructed by R3.4.3. Computational analysis was performed, and expression and interactions between the topological RNAs were detected by bioinformatics methods, real‐time quantitative PCR (qPCR), and luciferase assay. Cell proliferation ability was measured by 5‐ethynyl‐2′‐deoxyuridine (EdU) in MCs cultured under high‐ or low‐glucose conditions. Moreover, the effect of the topological key IncRNA histocompatibility 2 K region locus 2 (H2k2) H2k2 on MC proliferation via the miRNA (miR)‐449a/b/triplet motif 11 (Trim11)/Mek signaling pathway was examined by EdU, flow cytometry analysis, and Western blot. In total, 153 IncRNAs, 428 mRNAs, and 2242 interactions were included in the constructed DN‐related ceRNA network. There were 15 RNAs in the top 5% of degree and betweenness. The expression of IncRNA H2k2 and mRNA Trim11 in MCs was increased in DN, which is consistent with the results of RNA‐seq and real‐time qPCR in vivo and in vitro . miR‐449a and miR‐449b, which were down‐regulated in MCs cultured with high glucose, were selected for further analysis. The results of real‐time qPCR and luciferase assay revealed the IncRNA H2k2‐miR‐449a/b‐Trim11 interaction in MCs. In addition, the data showed that H2k2 regulates MC proliferation via the miR‐449ab/Trim11/Mek signaling pathway. Taken together, these results provide new insight into the association between the topological key IncRNA H2k2 in the DN‐related ceRNA network and the miR‐449a/b/Trim11/Mek signaling pathway during MC proliferation in DN.—Chen, W., Peng, R., Sun, Y., Liu, H., Zhang, L., Peng, H., Zhang, Z. The topological key IncRNA H2k2 from the ceRNA network promotes mesangial cell proliferation in diabetic nephropathy via the miR‐449a/b/Trim11/Mek signaling pathway. FASEB J. 33, 11492–11506 (2019). www.fasebj.org